LASERS : 1-kHz-repetition-rate femtosecond Raman laser. (31st July 2016) - Didenko, N V; Konyashchenko, A V; Kostryukov, P V; Losev, L L; Pazyuk, V S; Tenyakov, S Yu
Abstract: A femtosecond Raman laser utilising compressed hydrogen is experimentally investigated under pumping by radiation from a 1-kHz-repetition-rate Ti : sapphire laser. In the regime of double-pulse pumping, the conditions are determined, which correspond to the minimal energy dispersion of Stokes pulses. The optical scheme is realised, which is capable of ensuring the long-term stability of the average power of the first Stokes component with a variation of less than 2%. The Stokes pulses are produced with a pulse duration of 60 fs and energy of 0.26 mJ at a conversion efficiency of 14%.